2016
DOI: 10.1007/s13594-016-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of camel and bovine milk fermented by lactic acid bacteria isolated from traditional fermented camel milk (Chal)

Abstract: Chal is a traditional fermented product produced from spontaneously fermented camel milk which contains several bacterial species with potential usage in producing traditional dairy products and functional foods. The aims of this study were to isolate and identify predominant lactic acid bacteria (LAB) from Chal and investigate antioxidant activity of camel and bovine milk fermented by these isolates. Chal samples were collected from Turkman Sahra, Golestan Province, Iran. The protein hydrolysis was determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 31 publications
0
35
1
Order By: Relevance
“…The current study showed the broilers fed FCSM-1 diets had higher serum and liver antioxidative abilities compared with bird fed CSM diet. Previous studies have shown that fermented soy products and fermented camel milk had high levels of antioxidant activity along with the ability to scavenge free radicals in vitro (Soleymanzadeh, Mirdamadi, & Kianirad, 2016;Xu, Du, & Xu, 2015). So fermented feed might alleviate the tissue lipid peroxidation, enhance antioxidant capacity and decrease oxidative damage (Hu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed the broilers fed FCSM-1 diets had higher serum and liver antioxidative abilities compared with bird fed CSM diet. Previous studies have shown that fermented soy products and fermented camel milk had high levels of antioxidant activity along with the ability to scavenge free radicals in vitro (Soleymanzadeh, Mirdamadi, & Kianirad, 2016;Xu, Du, & Xu, 2015). So fermented feed might alleviate the tissue lipid peroxidation, enhance antioxidant capacity and decrease oxidative damage (Hu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their transient occurrence in the GI tract, dairy LAB can nonetheless influence the resident microbiome and exert host-specific health benefits [14]. In addition to human GIT, potential probiotic candidates have been recently isolated from different kinds of fermented milks [172][173][174][175][176], cheeses [177][178][179][180][181][182], and kefir. Even if rigorous guidelines define when a single microbe or microbial consortia can be properly qualified as probiotic [183], these studies provided the basis for the development of new functional foods and defined a cohort of strains which will be in future employed as therapeutic adjuvants for in vivo studies.…”
Section: The Renaissance Of Interest Towards Artisanal Fdfmentioning
confidence: 99%
“…The health-promoting effects of LAB have received much attention. Milk fermented by Leuconostoc mesenteroides shows high antioxidant activity; that is, 1,1-diphenyl-2-picrylhydrazyl (and 2, 2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging activities, as well as high overall acceptance values compared with samples fermented by other strains (Soleymanzadeh et al, 2016). Lactic acid bacteria isolated from camel milk can also be used to produce other fermented dairy products because of their high acidifying and proteolytic activities (Fguiri et al, 2016).…”
Section: Discussionmentioning
confidence: 99%